Sifat Papan Laminasi Kayu Randu (Ceiba pentandra (L.) Gaertn) dengan Variasi Pola Gergajian Lamina dan Arah Lapisan - Muhammad Navis Rofii; Prasetyo Prasetyo; Tomy Listyanto; Annisa Primaningtyas; Yustinus Suranto; T.A. Prayitno; Ragil Widyorini (Jurnal Ilmu Kehutanan, 2022)
Kapok wood (Ceiba pentandra (L.) Gaertn) is a low-density wood species that can become a light construction material in the form of laminated timber products. This study aimed to understand the properties of laminated timber from kapok wood at different sawing patterns of laminae and core layer orientation. This study used kapok wood produced from community forests and PVAc (Polyvinyl Acetate) resin as the binder to produce laminated timber. The laminated boards were manufactured from dried laminas, measuring 100 x 9.5 x 1.7 cm, and were glued together with the resin before being pressed and clamped with the pressure of 1 MPa for 12 hours. The dimension of the final laminated board was 100 x 38 x 5 cm. Before being cut for the physical and mechanical properties tests, the laminated boards were conditioned at room temperature for a week. The results indicated that sawing patterns had insignificant effects on moisture content, density, static bending properties, and bonding strength of laminated boards. The core layer orientation had a significant effect on the density and the modulus of rupture. Generally, laminated board from kapok wood with the parallel grain direction of the core layer resulted in higher static bending properties and...